Graphie Dash Inovasi Desain Papan Edukasi Interaktif untuk Pembelajaran Tabel dan Grafik Kelas II SD - Kirana Rahman; Hani R; Ghia Tri Jayanti; R Moch. Rizal Hafiyan; Handayani Madania Insani (Jurnal Desain Produk Nasional, 2026)
This study discusses the development of game-based learning media products as an effort to improve the understanding and motivation of elementary school students in the material of basic tables and graphs in Mathematics subjects. This study uses the Research and Development method, which refers to the development of models through the stages of literature studies, observations, needs analysis, application of methods, design, trials, and product evaluation. This study also utilizes the SCAMPER technique in the process of designing ideas and developing the form of learning media. The study was motivated by data findings from observations and short interviews at SDN Dadaha Tasikmalaya, which indicated a need for more interactive and enjoyable learning media in data presentation materials. The subjects of this study were homeroom teachers and students of class II B at SDN Dadaha Tasikmalaya. Data collection techniques were carried out through visitation sheets, visitation monitoring and evaluation sheets, interviews, trials, and validation and evaluation documents for educational design projects. Data were analyzed using qualitative descriptive analysis techniques. The purpose of this study is to develop learning media for table and graph materials that emphasize the basic visualization of data presentation. The result of this study is an interactive learning board based on a magnetic surface, designed through observational data and design brief. This product is expected to improve second-grade students' comprehension of tables and graphs as an innovative teaching aid.